Economic and environmental life cycle assessment of a short-span aluminium composite bridge deck in Canada. (10th August 2021) - Pedneault, Julien; Desjardins, Victor; Margni, Manuele; Conciatori, David; Fafard, Mario; Sorelli, Luca
Abstract: The costs to maintain Québec's infrastructure—most of which was built in the 1960s and 1970s—are considerable, and major maintenance and reconstruction will be required in the coming years. In recent years, aluminum associations promote the increase of aluminum use in infrastructure and especially in bridge construction. This research aims to investigate the advantages of using aluminum deck bridges, which require less maintenance than traditional materials due to the natural resistance to atmospheric corrosion of aluminum, despite their higher investment costs that may limit their deployment. More specifically, the study compares for the first time the life cycle costs and environmental impacts of an aluminum-steel composite deck with a more traditional concrete-steel composite deck and provides a parametrized model allowing practitioners and designers to perform screening life cycle assessment and cost of short span bridge based on our data and results. Results show that the initial cost of aluminum deck is double that of concrete deck, but the overall cost is actually four times lower over the entire life cycle. The environmental results demonstrate the benefits of aluminum deck. Our main recommendation for future decision making in road infrastructure management is therefore to systematically expand the scope of the analysis integrating a full life cycle thinking also including the effects from traffic diversion. Highlights: Life cycle cost of aluminium bridge deck is 77% less than concrete deck. Potential environmental impacts of aluminum bridge deck are lower over the entire life cycle. Traffic disturbances are responsible for most of the cost and environmental impacts. Life cycle thinking minimizes the risk of problem shifting in decision-making.